Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3892/ijo.2022.5394
|View full text |Cite
|
Sign up to set email alerts
|

Glioma‑neuronal interactions in tumor progression: Mechanism, therapeutic strategies and perspectives (Review)

Abstract: An increasing body of evidence has become available to reveal the synaptic and functional integration of glioma into the brain network, facilitating tumor progression. The novel discovery of glioma-neuronal interactions has fundamentally challenged our understanding of this refractory disease. The present review aimed to provide an overview of how the neuronal activities function through synapses, neurotransmitters, ion channels, gap junctions, tumor microtubes and neuronal molecules to establish communication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 119 publications
0
4
0
Order By: Relevance
“…7 ). Neuronal hyperactivity promotes glioma proliferation by activating ion channels through glutamate secretion (Hua et al, 2022). These hyperexcitable neurons induce evoked ESCs in glioma cells mediated by AMPAR (Venkataramani et al, 2019; Venkatesh et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…7 ). Neuronal hyperactivity promotes glioma proliferation by activating ion channels through glutamate secretion (Hua et al, 2022). These hyperexcitable neurons induce evoked ESCs in glioma cells mediated by AMPAR (Venkataramani et al, 2019; Venkatesh et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…During this process, neurons also released neuroligin-3 to activate the PI3K-mammalian target of rapamycin pathway in glioma cells and promote the proliferation of glioma cells. [ 91 ] Although there are no relevant studies demonstrating that CS promotes excitatory synapse formation, Tantillo et al [ 92 ] found that gamma aminobutyric acidergic (GABAergic) interneuron activity was reduced in mice after chronic visual deprivation, a specific form of CS, resulting in increased glioma proliferation in the primary visual cortex. Unlike excitatory information transmitted by glutamatergic synapses, GABAergic neurons are the main inhibitory neurons in the CNS.…”
Section: Mechanisms Linking Chronic Stress To the Hallmarks Of Gliomamentioning
confidence: 99%
“…Similarly, GBM cells can influence neurons through the secretion of non-synaptic glutamate [62,63] and can reduce the activation of inhibitory interneurons [64]. Gliomas may also increase the risk of epilepsy by influencing glutamatergic and GABAergic signalling in neurons [65], with studies in awake patients observing more neuronal excitability in the GBM-infiltrated cortex [59]. Short-range electrocorticography on the tumour-infiltrated cortex revealed functional remodelling of language circuits as some tumour regions with TSP-1 + tumour cells maintained functional connectivity with neurons.…”
Section: Neuronsmentioning
confidence: 99%